Dimensions of cognition, behaviour, and mental health in struggling learners: A spotlight on girls - Jacalyn Guy; Silvana Mareva; Grace Franckel; the CALM Team; Joni Holmes (Wiley, 2022)
Abstract Background Fewer girls than boys are identified as struggling at school for suspected problems in attention, learning and/or memory. The objectives of this study were to: i) identify dimensions of cognition, behaviour and mental health in a unique transdiagnostic sample of struggling learners; ii) test whether these constructs were equivalent for boys and girls, and; iii) compare their performance across the dimensions. Methods 805 school‐aged children, identified by practitioners as experiencing problems in cognition and learning, completed cognitive assessments, and parents/carers rated their behaviour and mental health problems. Results Three cognitive [Executive, Speed, Phonological], three behavioural [Cognitive Control, Emotion Regulation, Behaviour Regulation], and two mental health [Internalising, Externalising] dimensions distinguished the sample. Dimensions were structurally comparable between boys and girls, but differences in severity were present: girls had greater impairments on performance‐based measures of cognition; boys were rated as having more severe externalising problems. Conclusions Gender biases to stereotypically male behaviours are prevalent among practitioners, even when the focus is on identifying cognitive and learning difficulties. This underscores the need to include cognitive and female‐representative criteria in diagnostic systems to identify girls whose difficulties could go easily undetected.